PENGARUH MOTIVASI PETANI TERHADAP KEBERLANJUTAN CORPORATE FARMING DI KALURAHAN TRIMULYO KAPANEWON JETIS KABUPATEN BANTUL - Royyan 'Abiid; Alia Bihrajihant Raya; Ratih Ineke Wati (JSEP (Journal of Social and Agricultural Economics), 2021)
Corporate farming is an activity to manage a stretch of farmer's land in one management, considering that extensification is challenging to implement in Bantul Regency. research aims to (1) knowing the motivation of farmers in implementing corporate farming in Bantul Regency; (2) knowing the factors that influence the motivation of farmers in implementing corporate farming in Bantul Regency; (3) knowing the influence of motivation on the sustainability of corporate farming in Bantul Regency. The method used is a descriptive method with a quantitative approach. The sample used is 30 members of the corporate farming group, using a random sampling technique. Data were analyzed by proportion test, multiple linear regression, and simple linear regression. The results showed that most of the members of the corporate farming group had high motivation. Factors that positively affect farmers' motivation in implementing corporate farming include education level, side work, length of farming, membership status, farmer's attitude, role of farmer groups, and farmer's land ownership area. Motivation has a positive effect on the sustainability of corporate farming.